THE EFFECT OF ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) DISCLOSURE, AND GREEN ACCOUNTING ON STOCK RETURN: MODERATED BY INDEPENDENT BOARD OF COMMISSIONERS - Ayuni Fitria; Murtanto (ZILLZELL MEDIA PRIMA, 2024)
The objective of this research is to analyze the effect of Environmental, Social, Governance (ESG) disclosure and green accounting on stock returns with independent board of commissioners as moderation variable. The population of this research is energy sector companies listed on the Indonesia Stock Exchange (BEI) for the 2018-2022 period. The sampling technique uses purposive sampling. Based on predetermined criteria, 135 research data were obtained. This type of research is quantitative and the data used is secondary data. The analytical method used is panel data regression analysis using EViews software version 13.0. The panel data regression model used is the Common Effect Model (CEM). The results of this research show that ESG has a positive effect on stock returns, green accounting has a negative effect on stock returns, IBC cannot strengthen the effect of ESG on stock returns, and IBC weakens the effect of green accounting on stock returns.